Pollen and seed morphology of cleome species (Cleomaceae) in Vietnam - Nguyen, Nga Thi Thu; Chaudhary, Ritesh Kumar; Tu, Tan Quang; Chu, Mau Hoang; Nguyen, Quan Huu; Do, Hai Van; Tran, Bach The; Lee, Joongku; Lee, Changyoung; Sy, Thuong Danh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Cleomaceae is a family that includes 18 genera distributed worldwide in tropical and temperate regions. Cleome L. is the largest genus having 207 species, widely distributed in tropical and subtropical regions (POWO 2019). In Vietnam, the genus is represented by four species Cleome rutidosperma DC., C. houtteana Schltdl., C. viscosa L. and C. gynandra L. The present study documents the pollen and seed characteristics of all four species of Cleome in Vietnam, and the data obtained using light microscope and scanning electron microscope are analyzed considering their importance in taxonomic delimitation and understanding their phylogenetic relationship. The results indicated a close relationship between different pollen and aperture types. The striking differences between the pollen shapes among different species of Cleome could be useful in taxonomic and evolutionary studies. Similarly, seed shape and surface characters provided important clues for their delimitation. Based on the pollen and seed morphological characteristics, a taxonomic key has been provided for easy identification of the Cleome species in Vietnam.